MEMAHAMI KATEGORISASI PENDIDIKAN: Islam dan Umum dalam Perspektif Kebangsaan - Khunaifi, Agus (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: This paper is not research but the analysis is based on the logic of thedevelopment of the phenomenon of Islamic education in Indonesia today. Basic truthsthat are used more in the analytical logical truth . This paper aims to examine thedevelopment of Islamic education from the point of view of nationality. The focus ofthe study focused on the phenomenon of categorization between Islamic educationand general education in Indonesia. At the moment general and Islam categorizationare a reality of education in Indonesia. Islamic education as part of the nationaleducation has increased significantly lately. Islamic education on the one hand anincrease in contributed greatly to the education of the nation. But on the other handhas the potential to become the exclusive power to hinder the national education. Thisphenomenon requires a discussion of the whole in order to gain an understanding ofthe neutral. So this phenomenon is not a new issue that can impede the progress ofnational education.ÙØ°Ù Ø§ÙÙØ±ÙØ© ÙÙØ³Øª ÙØªÙØ¬Ø© ÙÙØ¨ØØ«Ø ÙÙÙÙ ÙØ³ØªÙØ¯ Ø§ÙØªØÙÙÙ Ø¹ÙÙ ÙÙØ·Ù Ø¸Ø§ÙØ±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§Ø§ÙÙÙÙ. Ø§ÙØÙÙÙØ© Ø§ÙØ£Ø³Ø§Ø³ÙØ© Ø§ÙØªÙ ÙØªÙ Ø§Ø³ØªØ®Ø¯Ø§ÙÙØ§ Ø£ÙØ«Ø± ÙÙ Ø§ÙØÙÙÙØ© Ø§ÙÙÙØ·ÙÙØ© Ø§ÙØªØÙÙÙÙØ©. ØªÙØ¯Ù ÙØ°Ù Ø§ÙÙØ±ÙØ© Ø¥ÙÙØ¯Ø±Ø§Ø³Ø© ØªØ·ÙÙØ± Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ ÙØ¬ÙØ© ÙØ¸Ø± Ø§ÙØ¬ÙØ³ÙØ©. Ø±ÙØ² ØªØ±ÙÙØ² Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹ÙÙ Ø¸Ø§ÙØ±Ø© ØªØµÙÙÙ Ø§ÙØªØ¹ÙÙÙ ÙÙØ¥ÙØ¯ÙÙÙØ³ÙØ§ Ø¨ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ§ÙØ¬ÙÙÙØ±. ØØ§ÙÙØ§ Ø§ÙØªØµÙÙÙ Ø§ÙØ¹Ø§Ù ÙØ§ÙØ¥Ø³ÙØ§Ù ÙÙ ÙØ§ÙØ¹ Ø§ÙØªØ¹ÙÙÙ ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§. ÙØ²Ø§Ø¯ Ø§ÙØªØ±Ø¨ÙØ©Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ¬Ø²Ø¡ ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙØ·ÙÙØ© Ø¨Ø´ÙÙ ÙÙØÙØ¸ ÙÙ Ø§ÙØ¢ÙÙØ© Ø§ÙØ£Ø®ÙØ±Ø©. Ø²ÙØ§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ ÙØ§ØÙØ© ØªÙÙØ±ÙØ³Ø§ÙÙØ© ÙØ¨ÙØ±Ø© ÙØªØ¹ÙÙÙ Ø§ÙØ£ÙØ©. ÙÙÙÙ ÙÙ ÙØ§ØÙØ© Ø£Ø®Ø±Ù ÙØ¯ÙÙ Ø§ÙÙØ¯Ø±Ø© Ø¹ÙÙ Ø£Ù ØªØµØ¨Ø ÙÙØ© ÙÙÙÙ Ø§Ù ØªÙÙØ¹ Ø§ÙØªØ¹ÙÙÙØ§ÙÙØ·ÙÙ Ø§ÙØØµØ±Ù. ÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø© ØªØªØ·ÙØ¨ ÙÙØ§ÙØ´Ø© ÙÙÙ ÙÙ Ø§Ø¬Ù Ø§ÙØØµÙÙ Ø¹ÙÙ ÙÙÙ ÙÙÙØØ§ÙØ¯Ø©. Ø°ÙÙ Ø£Ù ÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø©ÙÙØ³Øª ÙØ´ÙÙØ© Ø¬Ø¯ÙØ¯Ø© ÙØ¯ ØªØ¹ÙÙ Ø§ÙØªÙØ¯Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙØ·ÙÙØ©.